Food security status affects stress level and academic performance among university students - Awang, Syakirah; Mohd Abu Bakar, Wan Azdie (2018)
University students are vulnerable to experience food insecurity. This is due to their economic wellbeing in which their limited funds are not only for buying food, but also to pay for fees and other living expenses. Food expenditure is among the expenses that will be affected and reduced in order to survive at the university. Unfortunately, this situation results in food insecurity and subsequent consequences. A cross sectional study was conducted among students from Kulliyyah of Allied Health Sciences (KAHS) of IIUM Kuantan to assess the food security status and stress level among the population. Two hundred students were recruited as the participants in the study. The survey was conducted using the selfadministered questionnaire containing Food Insecurity Experienced Scale (FIES) and DASS 21 items. As food insecurity amplifies many nutritional, health and development impacts, this study also aimed to highlight any association of food insecurity with stress level and academic performance. Overall, 74.5% of KAHS students surveyed were food insecure. The study discovered a significant association between food insecurity and stress level (r=0.248, p<0.001). Besides, a negative association between food insecurity and academic performance was also revealed (r= -0.165, p=0.02). As a conclusion, food insecurity among university students may contribute to poor stress level and reduced academic performance. Actions need to be taken to improve the food security status to help the students to further excel in their studies.